Physico-chemical Processes at the Interface of Heterostructures Ag-Pd – Sn-Pb - Lepikh, Ya.I.; Lavrenova, T.I.; Snigur, P.O. (Physics and Chemistry of Solid State, 2021)
Physicochemical processes taking place at the interface of film elements (conductors) of hybrid integrated circuits, thick-film sensors and other microelectronic devices (MED) based on silver-palladium pastes and elements of standard soldering materials have been studied. Physicochemical mechanisms of processes of the material element mutual dissolution at the interface are proposed and analyzed. Conclusions are made that these processes affect the degradation of the electrophysical parameters and contact switch connections operational characteristics. It is established that the degradation main cause (partial or complete destruction of the contact connections on substrate ceramics (glass) Ag-Pd – Sn-Pb) is the functional film material significant dissolution in the Sn-Pb melt.